2005
DOI: 10.1158/1078-0432.ccr-04-2282
|View full text |Cite
|
Sign up to set email alerts
|

High Relapse Rate in Patients with MALT Lymphoma Warrants Lifelong Follow-up

Abstract: Background: B-cell lymphoma of the mucosa-associated lymphoid tissue (MALT lymphoma) is thought to be an indolent disease, with a good prognosis following various forms of treatment. Little, however, is known about the rate and pattern of relapse following successful treatment. Patients and Methods: We have analyzed time to and pattern of relapse in patients with MALT lymphoma, along with investigation of t(11;18)(q21;q21), t(1;14)(p22;q32), and t(14;18)(q32;q21) involving IGH/MALT1, trisomy 3, and trisomy 18.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
91
2
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(105 citation statements)
references
References 13 publications
8
91
2
4
Order By: Relevance
“…This is in contrast to 1 study indicating that it is not uncommon to develop disease recurrence late in the course of followup. 27 Recurrences of disease typically behave in an indolent manner, and prolonged survival was observed even after disease recurrence (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to 1 study indicating that it is not uncommon to develop disease recurrence late in the course of followup. 27 Recurrences of disease typically behave in an indolent manner, and prolonged survival was observed even after disease recurrence (Fig. 3).…”
Section: Discussionmentioning
confidence: 99%
“…When dissemination occurs, it is frequently to other mucosal sites. After therapy, relapse rates approached 40% in one retrospective analysis with a median follow-up of 47 months (range, 14-307 months); gastric MALT lymphomas were less likely to relapse than nongastric lesions (22% versus 48%) [22]. Rarely, the disease undergoes transformation to a more aggressive lymphoma type.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…(3) Despite their indolent behavior and excellent prognosis, MALT lymphomas do tend to relapse frequently. (13) In a study of pulmonary MALT lymphoma patients in long-term follow-up treatment, (11) it was reported that the overall survival of such patients was significantly worse than that observed in age-and gender-matched controls. Our report suggests that the disease progression is not always indolent.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of the t(11;18)(q21;21) translocation, which is particularly prevalent in patients with gastric (23.9%) and pulmonary (53.3%) MALT lymphomas, (12) does not seem to be related to disease recurrence. (13) Nor is there any evidence that this translocation is associated with chemotherapy resistance.…”
Section: Discussionmentioning
confidence: 99%